Hierarchical production planning and scheduling in a multi-product, batch process environment - Omar, M. K.; Teo, S. C. (TAYLOR & FRANCIS LTD, 4 PARK SQUARE, 2007)
This paper introduces a three-level hierarchical production planning and scheduling approach for multi-product and identical parallel machines in a batch process environment. The hierarchical approach extends the existing formulation and determines the optimal number of monthly batches that need to be scheduled, a process known in this industry as 'batching of orders'. At the top level of the hierarchy the approach deploys a mixed-integer linear programming model to solve the aggregate plans, where set-ups occur. At the second level, a weighted-integer goal programming model is developed to disaggregate the aggregate plans and provide an optimal number of monthly batches to be sequenced in presence of set-up time. At the bottom of the hierarchy, a job sequencing model is formulated, as a mixed-integer programming model that deals with sequencing of batches on parallel machines, with earliness and tardiness penalties and set-up time constraints. Real industrial data are used to test and validate the proposed models. Comparisons of models' results and company's actual performance indicate that, if the company implements our proposed approach, significant cost savings could be achieved.